Increasing the Growth and Yield of Okra (Abelmoschus esculentus) Plants with the Use of PGPR ( Plant Growth Promoting Rhizobacteria ) and Gibberellin - Krisna Bayu Prasetiyo; Didik Utomo Pribadi; Felicitas Deru Dewanti; Sri Wiyatiningsih (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Okra (Abelmoschus esculentus) is a horticultural crop rich in minerals, antioxidants, polyphenols, and flavonoids. One of the limiting factors for okra production is inadequate nutrition. The use of Plant Growth-Promoting Rhizobacteria (PGPR) and gibberellins is a promising approach to enhance okra production. This study aimed to determine the optimal concentrations of PGPR and gibberellin combinations for improving the growth and yield of okra. The experiment was conducted from March to June 2025 at the Experimental Field of the Faculty of Agriculture, Veteran National Development University, East Java. A factorial experiment was designed using a Randomized Block Design (RBD) with two factors: PGPR concentration at four levels (0 ml/l, 10 ml/l, 15 ml/l, and 20 ml/l) and gibberellin concentration at four levels (0 ppm, 100 ppm, 150 ppm, and 200 ppm), resulting in 16 treatment combinations, each replicated three times. The interaction between PGPR and gibberellin treatments significantly affected plant height and the number of flowers. The 20 ml/l PGPR treatment had the most significant positive effect on the number of leaves between 28 and 49 days after planting and on fruit weight during the 1st, 3rd, and 5th harvests. The 200 ppm gibberellin treatment significantly accelerated flower emergence, with an average of 35.39 days to flower emergence. The combination of 20 ml/l PGPR and 200 ppm gibberellin was the most effective treatment for enhancing okra plant growth and yield.